Interview with Manuel João Ramos - Ramos, M. (Stichproben - Vienna Journal of African Studies, 2021)
Interview on the production of a graphic essay on the early stages of the civil war in Ethiopia, that started on November 3rd, 2020. Its source material are on-the-ground testimonies detailing different views on the conflict. The essay makes use of the formal iconographic style of traditional Ethiopian painting to address the traumatic effects of the war in a way that may be immediately readable by Ethiopians, while offering non-Ethiopian readers, less familiarised with the conflict and with its political and symbolic underpinnings, the means to understand its multisided nature.